Penentuan Standar Spesifikasi Kerja di Café Berdasarkan Big Data dengan Metode LDA dan AHP - Christine Natalia; Ferdian Suprata; Feliks P S Surbakti; Sunny Clarence (Universitas Katolik Parahyangan, 2021)
A good human resources management practice will produce quality and quantity output for sustainable business. The employee recruitment process is a crucial initial stage to fulfil the needs of a quality employee. In this process, a company usually opens an advertisement for a job vacancy and selects based on job qualification requirements. This research contributes to determining job specification standards in a café or coffee shop based on Big Data analysis. Analysis has been done by Latent Dirichlet Allocation (LDA), and Analytical Hierarchy Process (AHP) method is implemented to select the type of works and work qualifications available in the food and beverages sector. Questionnaires and interviews have been conducted to collect primary data, and three leading websites of job seeker online platforms (Jobstreet.com, Gawean.id, and Lokerindonesia.com) are used as references in data collection. Finding gives information regarding four types of works in a cafe: manager, barista, chef, and waiter; eleven points for manager specifications, twelve points for barista specifications, eleven points for chef specifications, and fifteenth points for barista waiter specifications.